Dyspensa małżeńska w Nowym Kramsku w pierwszej połowie XIX wieku = Marital dispensation in Nowy Kramsk in the first half of the 19th century - Benyskiewicz, Krzysztof (1959- ) (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The correspondence between the parsons of Nowy Kramsk and the archbishop curia of Poznańis stored in the collections of Archive for Poznań Archdiocese. It concerns, among other things,the efforts for receiving marital dispensation. During the nearly sixty years' period between the year 1800 and 1858 twenty-one dispensation requests were filed. In most cases, the pleadings concerned obstacles to marriage stemming from the third or third connected with fourth degreeof kinship and relatedness.
Keywords: Nowe Kramsko (pow. babimojski); małżeństwo - katolicyzm; historia; 19 w.